Myocarditis Presenting with Ventricular Arrhythmias: Role of Electroanatomical Mapping-Guided Endomyocardial Biopsy in Differential Diagnosis - Pieroni, Maurizio; Smaldone, Costantino; Bellocci, Fulvio (IntechOpen, 2011)
None